Comparação de variedades de feijão utilizadas para produção de brotos comestíveis. - Nunes, Joseli Viviane Ditzel (2013)
In search of healthy food with high nutritional value and easy preparation, it has been using more frequently bean sprouts in the diet. Considering that the germination process is simple and money-saving, and that during germination the nutritional contents are larger than the grain ones, the objective of this study was identifying bean varieties that could be used for the production of food sprouts. We also wanted to compare them on physical, physiological, microbiological, and nutritional aspects, as well as verify their acceptability as new alternatives in a diet. In seeds, it was determined the water content, germination, vigor and water absorption curve. In sprouts and seeds, we done microbiological analyses. As result on the sprouts, it was quantified acidity, protein, iron, calcium, tannin and weight loss to determine the shelf life; the acceptability was measured by sensory analysis. The experimental design used was completely randomized with four varieties and four replicates per variety, and for the soaking curve it was performed polynomial regression. The seeds of mung bean and cowpea presented better physiological quality than other varieties. The mung bean got higher productivity, with a production referring to six times its initial mass. The beans did not obtain higher productivity due to the low vigor presented by the seeds. The production of sprouts with carioca and cowpea varieties was not significant, thus it is necessary to study new methodologies. The seeds and sprouts showed good microbiological quality. Higher levels of protein and iron were observed in mung sprouts, while the calcium and tannin were higher in azuki bean sprouts. The sprouts of mung bean and azuki obtained similar results for the sensory analysis parameters and had good acceptability by the tasters.